Cyber-Security Culture: Psychological and Legal Aspects - Begishev, I.R. (Psihologiâ i pravo, 2021)
Digitalization has become part and parcel of the modern-day human activities. Nowadays it is going into every field of business and personal life. To develop and prosper, most organizations need IT systems, and hence to take the safeguarding of their informational assets seriously. Many of the processes which are essential for securing their IT assets, largely depend on human interaction. This study has attempted to address the culture of cyber-security in the light of psychology and law. The results of the research showed that from the psychological standpoint, the culture of cyber-security involves the willingness on the part of a modern human to overcome the digital expansion by mastering the tools for countering the negative IT factors. In its turn, from the legal standpoint, the culture of cyber-security is based on the legislative framework which regulates the legal relations in the field of cyber-security. Цифровые технологии стали неотъемлемой частью современной деятельности человека. Сегодня они проникают во все сферы деловой и личной жизни. Большинству организаций для развития и процветания нужны информационные системы, и поэтому они должны серьезно относиться к защите своих цифровых активов. Многие процессы, необходимые для обеспечения безопасности цифровых активов, в значительной степени зависят от взаимодействия человека. В работе предпринята попытка осветить культуру информационной безопасности сквозь призму психологии и права. Результаты исследования показали, что с психологической точки зрения культура информационной безопасности включает готовность современного человека к преодолению цифровой экспансии за счет овладения им инструментарием противодействия негативным информационным факторам. В свою очередь, с правовой точки зрения культура информационной безопасности базируется на нормативно-правовой базе, регулирующей правоотношения в сфере кибербезопасности.